Can port state measures taken against RMFO partners be reconciled with international trade law? a critical analysis of the EU shared stocks regulation in light of the herring dispute - Auld, Kathleen (Department of Commercial Law, 2016)
The European Union (EU) and Faroe Islands, a small self-governing archipelago under the sovereignty of Denmark, both belong to the North-East Atlantic Fisheries Commission (NEAFC). NEAFC is a regional fisheries management organisation (RFMO) which is responsible for the management of, inter alia, Atlanto-Scandian herring. NEAFC parties have a long-term management plan in place for Atlanto-Scandian herring. Based on recommendations from the International Council for the Exploration of Seas (ICES) the parties set a total allowable catch (TAC) for the herring and divide this among the contracting parties each year. At the 2012 consultations between the NEAFC parties the Faroe Islands requested a larger share of the TAC. The Faroe Islands left the consultations after the other parties repeatedly refused this request. It was granted a share of the TAC by the other four states in its absence. It then set its own catch quota far above this allocated share. In response the EU put in place port state measures to prevent Atlanto-Scandian herring from entering the EU. This included an import ban and a ban on the use of EU ports by Faroese vessels. The EU took this action under Council Regulation (EC) No. 1026/2012 (Shared Stocks Regulation) which allows measures to be imposed against third countries that allow non-sustainable fishing of common or straddling stocks. This includes measures taken against RFMO partners for non-compliance with RMFO laws, as RFMOs are generally set up to conserve straddling fish stocks. This Regulation was promulgated in line with a number of multilateral environmental agreements (MEAs) such as UNCLOS and the United Nations Fish Stocks Agreement (UNFSA). The Faroe Islands challenged the Shared Stocks Regulation and the specific Implementing Regulation imposing the port state measures in both the World Trade Organisation (WTO) and a Tribunal constituted under the United Nations Convention on the Law of the Sea (UNCLOS). However the matter was settled before either of these tribunals could hear the case. The dissertation interrogates whether the EU Regulations are consistent with WTO law, specifically the General Agreement on Tariffs and Trade (GATT), using the facts of the Atlanto-Scandian herring dispute. Chapter I sets out the background to the dispute, and explains the concepts of illegal, unreported and unregulated (IUU) fishing, and port state measures. Chapters II and III of the dissertation consider the consistency of the EU Regulations with the GATT. Chapter II finds that the EU Regulations contravene one or more of Articles I, V and XI of the GATT (the substantive provisions). Chapter III considers whether these measures, having contravened one of the GATT substantive provisions, may be justified under Article XX of the GATT (the exceptions provision). Chapter III concludes that, although well-crafted, the EU Regulations may still not be justifiable under the Article XX Chapeau in the particular circumstances of the herring dispute, based on principles in previous WTO cases. Chapter IV considers the relationship between multilateral environmental agreements (MEAs) relevant to IUU fishing and WTO agreements, to determine whether the EU Regulations could be considered GATT-consistent by reference to these MEAs or whether the MEAs could override WTO law. Chapter V concludes.